Effectiveness of E-learning in the Engineering-related Lessons in the Math Course amongst the Higher Basic School Students in Jordan from the Teachers’ Perspective - Dr. Hamzeh Ahmad Abdelrahman Alqiam (Journal of Educational and Human Sciences, 2022)
This study explored the effectiveness of employing an e-learning platform for giving online engineering-related lessons in the math course for the higher basic school students from the teachers’ perspective. The researcher adopted a descriptive analytical approach and designed a survey that is based on the five point Likert scale. He chose a purposive sample consisting from 95 female and male math teachers. Those teachers were chosen from 95 public schools located in Jordan. Those schools were chosen from three Jordanian cities (Irbid, Amman and Karak). Those cities represent the Central, Northern, and Southern Provinces. The sampled schools include: 35 schools in Amman, 30 schools in Karak and 30 schools in Irbid.   The researcher passed the questionnaire forms to the chosen teachers through WhatsApp Application. All the passed forms were filled and analysed. It was found that it’s very effective to employ the e-learning platform for giving online engineering-related lessons in the math course for the higher basic school students from the teachers’ perspective. The researcher recommends holding courses for math teachers about the instructional strategies used for delivering online education in the math course.